Differential Expression of LncRNA in Bladder Cancer Development - Lorenzo Spirito; Rufina Maturi; Sara Carmela Credendino; Celeste Manfredi; Davide Arcaniolo; Marco De Martino; Francesco Esposito; Luigi Napolitano; Francesco Di Bello; Alfredo Fusco; Pierlorenzo Pallante; Marco De Sio; et al. (Diagnostics, 2023)
Bladder cancer (BC) is the tenth most common cancer, with urothelial carcinoma representing about 90% of all BC, including neoplasms and carcinomas of different grades of malignancy. Urinary cytology has a significant role in BC screening and surveillance, although it has a low detection rate and high dependence on the pathologist’s experience. The currently available biomarkers are not implemented into routine clinical practice due to high costs or low sensitivity. In recent years, the role of lncRNAs in BC has emerged, even though it is still poorly explored. We have previously shown that the lncRNAs Metallophosphoesterase Domain-Containing 2 Antisense RNA 1 (MPPED2-AS1), Rhabdomyosarcoma-2 Associated Transcript (RMST), Kelch-like protein 14 antisense (Klhl14AS) and Prader Willi/Angelman region RNA 5 (PAR5) are involved in the progression of different types of cancers. Here, we investigated the expression of these molecules in BC, first by interrogating the GEPIA database and observing a different distribution of expression levels between normal and cancer specimens. We then measured them in a cohort of neoplastic bladder lesions, either benign or malignant, from patients with suspicion of BC undergoing transurethral resection of bladder tumor (TURBT). The total RNA from biopsies was analyzed using qRT-PCR for the expression of the four lncRNA genes, showing differential expression of the investigated lncRNAs between normal tissue, benign lesions and cancers. In conclusion, the data reported here highlight the involvement of novel lncRNAs in BC development, whose altered expression could potentially affect the regulatory circuits in which these molecules are involved. Our study paves the way for testing lncRNA genes as markers for BC diagnosis and/or follow-up.